Union Complaints in Industrial Relations Negotiations - Walker, Esther (HERMES - Journal of Language and Communication in Business, 1993)
This paper details the design features of a potentially highly confrontational sequence of activities which is found in formal, industrial relations negotiations: a union complaint followed by a management defence. It is observed that the complaint is accomplished implicitly and that that implicitness is a joint accomplishment of all the participants; they collaborate to ensure that the talk constitutes and facilitates cooperative discussion, thereby avoiding confrontation. Through the description of this phenomenon, the author builds an account of how the participants' orientation to 'doing negotiation' inheres in the design of the talk.